Councillor ethics: a review of the Committee on Standards In Public Life's 'Local Government Ethical Standards'. Issue 5 (3rd July 2020) - Rose, Jonathan; Copus, Colin
ABSTRACT: The Committee on Standards in Public Life's (CSPL) 2019 report Local Government Ethical Standards presents a detailed review of local government ethics in England, aiming to highlight both best practice and areas for improvement. In so doing, it makes 26 recommendations ranging in importance. Likely to be one of the most important, and most controversial, is a recommendation to allow local authorities to suspend democratically-elected councillors for up to six months. This paper presents a review of the report and its recommendations, with a particular emphasis on the 'values-versus-compliance' distinction in ethical regulation. IMPACT: Policy-makers and practitioners are often faced with difficult choices concerning ethical regulation, and attempts to improve ethical regulations can sometimes cause new and unexpected problems. The authors review the Committee on Standards in Public Life's report Local Government Ethical Standards, placing the ethical challenges and opportunities for unintended consequences into the values-vs-compliance framework. The paper will be useful for policy-makers and regulators concerned with local government in England, who may be charged with implementing aspects of this report, while the broader issues discussed about the challenges of ethical regulations and the limits of compliance-based policies will be useful in a wide range of contexts and countries.